(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
Jatropha heynei of family Euphorbiaceae is an endemic herb with ethno-medicinal values. The present study investigates the phytochemical profiling, in-vitro anticancer activity against Dalton’s lymphoma ascites (DLA) and ehrlich’s ascites carcinoma (EAC) cell lines and in-silico molecular docking analysis of isolated chemicals of J. heynei tuber ethanolic extract. High resolution liquid chromatograph mass spectrometer (HR-LCMS) analysis of ethanolic tuber extract revealed the presence of 19 prominent phytochemical compounds. Six compounds meptazinol, 8-amino-7-oxononanoate, dihydrodeoxystreptomycin, albendazol (II), hydroxytinidazole, azoprocarbazine were present in high quantity, of which azoprocarbazine was shown with anticancer activity. There were several compounds with a number of other therapeutic properties. The ethanolic extract of J. heynei tuber showed significant in-vitro cytotoxic activity against DLA (IC50=64.14 μg mL-1) and EAC (IC50=71.42 μg mL-1) cancer cell lines, almost comparable to the value of standard curcumin (IC50=54.36 μg mL-1). Molecular docking and in-silico analysis of the compounds such as azoprocarbazine, ecgonine and meptazinol displayed strong interactions with the anticancer target proteins such as vascular endothelial growth factor (VEGF), tyrosine kinase (TK), and matrix metalloproteins (MMP) when compared with their respective drug inhibitors pazopanib, imatinib and batimastat. Compounds with wide range of biological activities suggested that J. heynei could be exploited for formulating new drugs in the treatment of several diseases and disorders.